The effect of adrenaline concentration in lidocaine on prehypertension patients during tooth extraction: an observational analysis - Hermanto, Eddy; Arjanti, Hanifah; Laihad, Fanny M.; Pranoto, Amelia Elizabeth; Sari, Rima Parwati; Krisna, Indra Hadi (Universitas Padjadjaran, 2026)
Introduction: Prehypertension refers to a systolic value 120–139 mmHg or diastolic value 80–90 mmHg. Studies have shown that the prevalence of prehypertension is over 30% among young adults. The extraction procedure was performed using lidocaine and adrenaline as anesthetics. The purpose of this study was to analyze the effect of adrenaline concentration in lidocaine on prehypertension patients during tooth extraction. Methods: This is a prospective analytical observational study with a pre–post measurement design. This study was conducted on 36 prehypertensive patients who were divided into 3 groups. Blood pressure was measured before and less than 5 minutes after administration of lidocaine 2% local anesthesia with either 1:80,000, 1:100,000 or 1:160,000 adrenaline, using a calibrated digital tensimeter (TensiOne 1A). Data were analyzed using paired t-tests. Results: Homogeneity test: systole before 0,033, systole after 0,329, diastole before 0,174, diastole after 0,274. Anova test: systole before 0,685, systole after 0,837, diastole before 0,03, diastole after 0,058. Post hoc results showed there were statistically significant differences in diastolic blood pressure in the 1:100.00 and 1:160.000 group before diastole. Before performing the one-way ANOVA and paired t-test, the data were assessed for normality using the Shapiro–Wilk test, which indicated a normal distribution (p > 0.05). Statistical analysis was then conducted using paired t-tests and one-way ANOVA, followed by post hoc testing. Conclusion: The administration of 2% lidocaine with adrenaline concentrations of 1:80,000, 1:100,000, and 1:160,000 did not produce meaningful changes in blood pressure in prehypertensive patients undergoing closed-method dental extraction